Gender differences in victims of war torture: Types of torture and psychological consequences - Špirić Željko; Opačić Goran; Jović Vladimir; Samardžić Radomir; Knežević Goran; Mandić-Gajić Gordana; Todorović Milorad (Vojnosanitetski Pregled)
Background/Aim. Torture for political reasons is an extreme violence in interpersonal relations resulting in not only acute psychiatric disorders but also very often in very severe and far reaching negative consequences for the overall psychosocial functioning of a victim. The aim of this study was to investigate gender differences in types of torture and psychological consequences in subjects who experienced war torture. Methods. A sample (410 men and 76 women) included clients of 'Centre for rehabilitation of torture victims - IAN, Belgrade' who experienced torture in prisons and concentration camps during civil wars in ex-Yugoslavia 1991-1995 and 1999. Types of Torture Questionnaire with 81 items was used for collecting data about forms of torture. Symptom Checklist 90-Revised (SCL-90- R) was used for assessing type and intensity of psychological symptoms, and Impact of Event Scale (IES) was used to estimate posttraumatic complaints. Results. A gender difference was found for 33 types of torture: 28 more frequent in men, and 5 in women. Factor analysis of torture types revealed three factors explaining 29% of variance: 'common torture', 'sadistic torture', and 'sexual torture'. Discriminant analysis revealed significant gender difference concerning the factors. 'Common torture' and 'sadistic torture' were more prominent in men, and 'sexual torture' was more present in women. Higher scores on depression, anxiety, somatization, interpersonal sensitivity and obsessive-compulsive dimensions on SCL-90-R were found in women. General score and scores of subscales (intrusion and avoidance) on IES were significantly higher in women. Conclusion. Women exposed to war torture experienced less torture techniques and shorter imprisonment than men, but had more frequent and severe symptoms of posttraumatic stress disorder and other psychological symptoms. Gender differences in posttraumatic symptomatology can not be explained exclusively by gender differences in types of torture found in this study.